THE USE OF INNOVATIVE TECHNALOGIAYAS IN TEACHING EDUCATIONAL SCIENCE IN GENERAL SECONDARY SCHOOLS (American Journal of Technology and Applied Sciences, 2022)
We hope that this article will be useful to many of them in the field of scientific observations on the use of innovative technologies in teaching educational science in general secondary schools.